1974
DOI: 10.1073/pnas.71.7.2777
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of a Pyrimidine Dimer Repair Mechanism in Mammalian Mitochondria

Abstract: We have investigated whether mammalian cells can repair pyrimidine dimers in their mitochondrial DNA which have been induced by ultraviolet light. The assay system is based upon the ability of the phage T4 UV endonuclease to nick covalently closed circular mitochondrial DNA that contain pyrimidine dimers. Our At least three modes of repair of ultraviolet light-damaged DNA exist in prokaryotic cells: photoreactivation, dimer excision repair, and postreplication repair (1-3). In placental mammalian cells, exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
238
1
5

Year Published

1988
1988
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 456 publications
(259 citation statements)
references
References 14 publications
7
238
1
5
Order By: Relevance
“…The steady-state concentration of oxygen radicals may be even higher in tumor mitochondria since they have diminished amounts of superoxide dismutase [53,54] There is a general consensus that mitochondria are less efficient in repairing DNA damage and replication errors than the nucleus [56][57][58][59]. For example, they lack excision repair and recombinational repair [60,61]. Mitochondria do, however, possess three uracil DNA glycosylases [62][63][64], two endonuclease activities specific for apurinic/ apyrimidinic sites [Tomkinson, A.E.…”
Section: Mitochondria and Oxygenmentioning
confidence: 99%
“…The steady-state concentration of oxygen radicals may be even higher in tumor mitochondria since they have diminished amounts of superoxide dismutase [53,54] There is a general consensus that mitochondria are less efficient in repairing DNA damage and replication errors than the nucleus [56][57][58][59]. For example, they lack excision repair and recombinational repair [60,61]. Mitochondria do, however, possess three uracil DNA glycosylases [62][63][64], two endonuclease activities specific for apurinic/ apyrimidinic sites [Tomkinson, A.E.…”
Section: Mitochondria and Oxygenmentioning
confidence: 99%
“…The accumulation of deleterious mutations in the mitochondrial genome has also been proposed to be important in aging (2)(3)(4)(5). It was known that some types of DNA damage occur at higher levels in mitochondrial DNA (mtDNA) and that mitochondria are deficient for some types of DNA repair; some repeated nuclear sequences also show such a deficiency (11)(12)(13)(14). But assays with the sensitivity to detect the basal level of some types of mitochondrial mutation in normal human tissues have only recently been developed (5,15,16).…”
mentioning
confidence: 99%
“…Such views were based on early experiments showing that UV-induced pyrimidine dimers were not repaired in mtDNA (28). However, subsequent studies have demonstrated that certain types of damage to DNA bases resulting from deamination, simple alkylation and oxidation can be efficiently repaired in mitochondria (reviewed in 29-31).…”
Section: Mitochondrial Dna Damage and Repairmentioning
confidence: 99%